Vaccination Perception and Attitude among Undergraduate Medical and Teacher Education Students at Charles University, Prague, Czech Republic - Šálek, Jiří; Čelko, Alexander M; Dáňová, Jana (Vaccines, 2020)
This cross-sectional comparative study was designed to evaluate different opinions and their impact on vaccine confidence, as perceived by students of two different university programs (medicine and teacher education), as both of them play important roles in patient education, with the latter major shaping the skills of critical thinking. Multi-item, opinion-based, paper-and-pencil anonymous questionnaires were distributed among students of medicine and teacher education. Data were sorted and divided into two sets to be analyzed using logistic regression. Out of a total of 722 respondents, 386 were medical students and 336 were teacher education students. While most respondents said they were not in favor of alternative medicine, a significantly higher number of alternative medicine followers were teacher education students. The positive vaccination perception rate (PVPR) is not dependent on the behavioral factors of student respondents (irrespective of their major) but is largely affected by their attitude to alternative medicine. Fear of infection dramatically increased the PVPR (up to 6.7 times) in those who were versus were not afraid of getting infected or were not quite sure whether to fear it. Fear of side effects of vaccination clearly decreased the PVPR, by at least 84%.
Keywords: attitudes; education; immunization; confidence; vaccination perception; Czech Republic; public health; undergraduate students; vaccination